IMPLEMENTASI KEBIJAKAN SISTEM ZONASI DALAM PENERIMAAN PESERTA DIDIK BARU SMAN 4 WAJO - Hayanuddin, Hendra; Parawangi, Anwar; Syukri, Syukri (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
Implementation of the Zoning System Policy in Student Admissions is a policy for equal access and quality of education because the principle is to bring education services closer to the community and equalize the quality of education. The zoning system provisions contained in the Acceptance of New Students (PPDB) are based on Permendikbud Number 44 of 2019 concerning Acceptance of New Students in Kindergartens, Elementary Schools, Junior High Schools, High Schools and Vocational High Schools. This study aims to find out how the zoning system policy is implemented in accepting new students at SMA Negeri 4 Wajo. The type of research used is qualitative research with a descriptive approach by obtaining data from interviews, observation and direct documentation in the field. The results of this study indicate that the implementation of the zoning system policy in PPDB SMA Negeri 4 Wajo has been going quite well when viewed from various indicators, namely communication, resources, disposition and bureaucratic structure, only the communication that has been carried out has not gone well. This can be seen from the research results of researchers associated with George C. Edward III's 4 indicators including communication, resources, disposition and bureaucratic structure.